RELEVANSI AJARAN ENSIKLIK SPE SALVI BAGI PENDERITAAN - Alfanay, Finsen (LOGOS: JURNAL PENDIDIKAN KEAGAMAAN KATOLIK, 2021)
This paper is a of qualitative research. It aims to describe the concept of hope according to Pope Benedict XVI in his Encyclical Spe Salvi and its relevance to the reality of human suffering. The main question of this paper is: “What is the relevance of the teachings of the Encyclical Spes Salvi to the suffering of modern humans?” This paper maintains the idea that suffering is part of human existence, and is closely related to human sin and limitations. However, hope changes the way individuals and communities view suffering. Christian hope encourages concrete actions for social justice and spiritual renewal, gives courage, purifies and strengthens faith, increases solidarity and compassion in the community. This encyclical teaches that hope is an active force that encourages personal and communal transformation, concrete action, and social solidarity, creating a stronger and more loving community.